Outcomes of Wide Awake Local Anaesthesia no Tourniquet (WALANT) In Soft Tissue Surgeries Of The Hand - Panthee, Rajan; Kumar Gupta, Mithilesh; Nepal, Santosh; Kafle, Gokul; Kumar Sah, Raj; Mahato, Ajay (Birat Journal of Health Sciences, 2024)
Introduction: Hemostasis in hand surgery can be achieved by use of an arm tourniquet but it has its own disadvantages like tourniquet-related pain, muscle and nerve injury, post-tourniquet thrombosis, and bleeding. Another method can be the use of epinephrine locally, but surgeons are concerned with digital ischemia and necrosis as seen with use of procaine in the 1970s. Recently Wide Awake Local Anesthesia No Tourniquet (WALANT) is being popular among hand surgeons in which a mixture of local anesthetic with adrenaline and sodium bicarbonate is used. Despite the absence of tourniquet related complications in WALANT technique, surgeons are reluctant to use lignocaine with epinephrine in hand surgery. Objectives: The objective of this study is to observe the outcomes of WALANT technique in various surgical procedures of hand. Methodology: This prospective study involved 103 patients undergoing soft tissue surgery of the hand at Birat Medical College Teaching Hospital. Patients meeting inclusion criteria and willing to participate in study were included. A proforma was filled by the operating surgeon and another proforma was to be filled by patient at home after discharge which was retrieved at follow-up visit. A mixture of 10 ml of 2% lignocaine with adrenaline diluted in equal volume of normal saline and 2ml of 8.4% sodium bicarbonate was used for local anesthesia. None of our patients developed digital ischemia or necrosis, one patient developed surgical site infection which recovered with oral antibiotics. The mean VAS score at the time of administration of local anesthesia was 3.8+1.2, intraoperatively it was 1.8+ 1.1 and at 2 hours postoperatively it was 2.3+1.3. VAS score at 6 hours, 12 hours and 24 hours postoperatively was 3.2+1.2, 3.4+1.4 and 3.7+1.1 respectively. Hemostasis control was excellent in 33 cases, very good in 58 cases, good in 8 cases, and poor in 4 cases. Conclusion: We conclude that WALANT technique is safe to use in various soft tissue surgeries of hand surgery in terms digital ischemia, necrosis or wound infection and effective in providing excellent control of hemostasis at surgical site.